Genomic epidemiology of Corynebacterium striatum from three regions of China: an emerging national nosocomial epidemic. (April 2021) - Wang, X.; Zhou, H.; Du, P.; Lan, R.; Chen, D.; Dong, A.; Lin, X.; Qiu, X.; Xu, S.; Ji, X.; Li, M.; Hou, X.; et al.
Summary: Background: Corynebacteritum straitum has been considered as an emerging multi-drug-resistant (MDR) pathogen. Isolation of MDR C. striatum as the only organism from respiratory samples from hospitalized patients is increasing in China. Aim: To elucidate the genomic epidemiology and evolution of C . striatum in China. Methods: A total of 260 isolates from 2016 to 2018 were collected from three hospitals in three regions of China. Antibiotic sensitivity testing was performed on all isolates. Whole-genome sequencing was applied to all isolates to assess their genomic diversity and relationships and detect the presence of antimicrobial resistance genes (ARG) and ARG cassettes. Findings: Almost all isolates (96.2%, 250/260) showed multi-drug-resistance. Genome sequencing revealed four major lineages with lineage IV emerging as the epidemic lineage. Most of the diversity was developed in the last 6 years. Each hospital has its own predominant clones with potential spread between Hebei and Guangdong hospitals. Genomic analysis further revealed multiple antimicrobial resistance genes. Conclusions: Our results suggested that four lineages of C. striatum have spread in parallel across China, causing persistent and extensive transmissions within hospitals. MDR C. striatum infection has become a national epidemic. Antibiotic-driven selection pressure may have played significant roles in forming persistent and predominant clones. Our data provide the basis for surveillance and prevention strategies to control the epidemic caused by MDR C. striatum .